Ventral striatal dopamine synthesis capacity is associated with individual differences in behavioral disinhibition - Lawrence, Andrew D.; Brooks, David (Frontiers in Behavioral Neuroscience, 2014)
Pathological gambling, alongside addictive and antisocial disorders, forms part of a broad psychopathological spectrum of externalizing disorders, which share an underlying genetic vulnerability. The shared externalizing propensity is a highly heritable, continuously varying trait. Disinhibitory personality traits such as impulsivity and novelty seeking (NS) function as indicators of this broad shared externalizing tendency, which may reflect, at the neurobiological level, variation in the reactivity of dopaminergic (DAergic) brain reward systems centered on the ventral striatum (VS). Here, we examined whether individual differences in ventral striatal dopamine (DA) synthesis capacity were associated with individual variation in disinhibitory personality traits. Twelve healthy male volunteers underwent 6-[18F]Fluoro-L-DOPA (FDOPA) positron emission tomography (PET) scanning to measure striatal DA synthesis capacity, and completed a measure of disinhibited personality (NS). We found that levels of ventral, but not dorsal, striatal DA synthesis capacity were significantly correlated with inter-individual variation in disinhibitory personality traits, particularly a propensity for financial extravagance and irresponsibility. Our results are consistent with preclinical models of behavioral disinhibition and addiction proneness, and provide novel insights into the neurobiology of personality based vulnerability to pathological gambling and other externalizing disorders.